Illnesses during 11 international athletics championships between 2009 and 2017: incidence, characteristics and sex-specific and discipline-specific differences - Edouard, P.; Junge, A.; Sorg, M.; Timpka, T.; Branco, P. (British Journal of Sports Medicine, 2019)
Background: Illnesses impair athletes` participation and performance. The epidemiology of illness in athletics is limited. Objective: To describe the occurrence and characteristics of illnesses during international athletics championships (indoor and outdoor), and to analyse differences with regards to athletes` sex and participation in explosive and endurance disciplines. Methods: During 11 international championships held between 2009 and 2017, physicians from both national medical teams and the local organising committees reported daily on all athlete illnesses using a standardised report form. Illness frequencies, incidence proportions (IPs) and rates (IRs), and relative risks (RR) with 95% CIs were calculated. Results: During the 59 days of the 11 athletics championships, 546 illnesses were recorded in the 12 594 registered athletes equivalent to IP of 43.4 illnesses per 1000 registered athletes (95% CI 39.8 to 46.9) or IR of 1.2 per 1000 registered athlete days (95% CI 1.1 to 1.2). The most frequently reported illnesses were upper respiratory tract infections (18.7%), exercise-induced fatigue/hypotension/collapse (15.4%) and gastroenteritis (13.2%). No myocardial infarction was recorded. A total of 28.8% of illnesses were expected to lead to time loss from sport. The illness IP was similar in male and female athletes, with few differences in illness characteristics. During outdoor championships, the illness IP was higher in endurance than explosive disciplines (RR=1.87; 95% CI 1.58 to 2.23), with a considerably higher IP of exercise-induced illness in endurance disciplines, but a similar upper respiratory tract infection IP in both discipline groups. Conclusions: Illness prevention strategies during international athletics championships should be focused on the most frequent diagnoses in each discipline group.